Influence of Post-Weld Heat Treatment on the Mechanical Properties and Microstructure of a Seamless Pipe of an ASTM A335 Gr P91 Steel - Bento, Emerson André Pinto; Torres, Edwar Andrés; Chemin, Aline Emanuelle Albuquerque; Dos Santos Maciel, Carla Isabel; Caselatto, Alexandre Lourenção; Ruchert, Cassius Olívio Figueiredo Terra; Avila, Julian Arnaldo [UNESP] (FapUNIFESP (SciELO), 2025)
This study investigates the effects of different post-weld heat treatments (PWHT) on the mechanical properties and microstructure of ASTM 335 Gr P91 martensitic steel, commonly used in boiler applications. Mechanical tests were conducted at room temperature, 300°C, and 600°C. Two PWHT conditions were applied: (i) PWHT-1, involving a 300°C isothermal treatment followed by heating to 770°C, and (ii) PWHT-2, following the same profile but without cooling to room temperature after the initial isothermal step. The resulting microstructure exhibited martensitic features, with a gradient of prior austenite grain boundaries in the heat-affected zone (HAZ) and δ-ferrite formation in the fusion zone (FZ), reducing toughness. Ultimate tensile strength decreased with increasing temperature, ranging from 675–750 MPa (RT), 525–615 MPa (300°C), and 375–440 MPa (600°C). Elongation was highest at 600°C (BM: 25–30%, FZ: 8–20%), decreasing at room temperature (BM: 20–25%, FZ: 2–12%). Toughness tests showed crack propagation across BM, HAZ, and FZ, with the lowest energy absorption in FZ (0.05–0.4 mm, 12–50 J). At 600°C, toughness decreased in BM and HAZ but increased in FZ, suggesting a change in deformation mechanisms at elevated temperatures.
Keywords: High-Temperature Performance; Martensitic CrMo Steel; Mechanical Properties; Microstructure Evolution; Post-Weld Heat Treatment (PWHT)